Síntese, caracterização físico-química e estudo da atividade antitumoral de complexos ternários de Cu(II) com um antibiótico e uma alfa,alfa-diamina e de Ru(II) com alfa,alfa-diaminas - Priscila Pereira Silva (2013)
Eight new complexes were prepared, six of Cu(II) and two of Ru(II): [Cu(phen)(dox)(H2O)(ClO4)](ClO4) (1); [Cu(phen)(tc)(H2O)(ClO4)](ClO4) (2); [Cu(phen)(Shyd)(acn)(ClO4)](ClO4) (3); [Cu(bpy)(Shyd)(acn)(ClO4)](ClO4) (4); [Cu(phen)(Ohyd)(acn)(ClO4)](ClO4) (5); [Cu(bpy)(Ohyd)(acn)(ClO4)](ClO4) (6); [Ru(phen)(pdShyd)(dmso)Cl](PF6) (7) and [Ru(phen)(pdOhyd)(dmso)Cl](PF6) (8). The ligands used were the N-heterocyclic donors 1,10-phenanthroline (phen) and 2,2 '-bipyridine (bpy), the antibiotics doxycycline (dox) and tetracycline (tc), the hydrazides of 2-thiophenecarboxylic acid (Shyd) and 2-furoic acid (Ohyd) and two novel N-heterocyclic donors: N'-(6-oxo-1,10-phenanthroline-5(6H)-ylidene)thiophene-2-carbohydrazide (pdShyd) and N'-(6-oxo-1,10-phenanthroline-5(6H)-ylidene)furan-2-carbohydrazide (pdOhyd). The complexes were characterized by elemental analysis, conductimetry, UV-vis and IR spectroscopy, EPR (for copper complexes), NMR (for ruthenium complexes), single crystal X-ray diffraction (for complexes 3, 5 and 6) and mass spectrometry (for complexes 1, 2, 7 and 8). The cytotoxic effect of all complexes and ligands in a chronic myelogenous leukemia cell line was studied. Exposure to UV-A irradiation enhances the cytotoxic activity of all complexes. The cytotoxic activity of these complexes correlated well with the intracellular concentration of copper and the number of Cu-DNA adducts formed inside the cells. Complexes 1 and 2 present an expressive plasmid DNA cleacage activity generating single and double-strand breaks, under mild reaction conditions, and even in the absence of any additional oxidant or reducing agent. Spectrophotometric titrations with CT-DNA indicated that all complexes bind to this macromolecule. They are the most potent DNA cleavage agents reported so far. The administration of complex 1 retards the appearance of Ehrlich tumor inoculated in mice.